In vitro embryo rescue of interspecific hybrids of Lepidium - Reyes Estevez, Estefany (2021)
With the ongoing climate change and growing world population, there is an increasing demand for vegetable oils for industrial and food purposes. Lepidium campestre (field cress) is a wild cruciferous, which is currently under domestication as a new potential high-yielding oil crop for cold climate conditions. Because of problems with early shattering silicles and low oilseed content, there is an initiative to cross the crop with relatives L. draba and L. graminifolium, to achieve a hybrid with shattering resistance and a higher oilseed content. Because of hybrid incompatibility, the hybridization of these species is difficult to achieve with traditional breeding methods. In an attempt to produce a protocol for the successful interspecific crossings of L. campestre x L. draba and L. campestre x L. graminifolium, ovary culture and direct embryo culture, were performed, and various maturity-degrees at the date of harvest were tested. A self-pollinated L. campestre control produced an embryo which developed in vitro, but no hybrid embryos were achieved in the interspecific crosses. It was concluded that experiments with pre-fertilization methods, reciprocal crossing, and more culture media compositions are needed to successfully develop a method for embryo rescuing to obtain interspecific hybrids of L. campestre x L. draba and L. campestre x L. graminifolium.